Practising entrepreneuring as emplacement: the impact of sensation and anticipation in entrepreneurial action. Issue 3 (14th March 2020) - Antonacopoulou, Elena P.; Fuller, Ted
ABSTRACT: We extend the Entrepreneurship as Practice debate by making the case for the lived experience of entrepreneuring, i.e. when entrepreneurship is practised as part of the everyday, seizing moments that define action as entrepreneurial. We focus not only on the enactment and embodiment of entrepreneurial practices but also their emplacement . Emplacement goes beyond context, process and practice in entrepreneuring, to account for ways entrepreneurial practices are formed, performed and transformed when grounded in the sensations . Such sensuousness gives in turn practical support to entrepreneurial action in the anticipation that defines what is deemed a suitable response given the eco-system being co-created. This focus on emplacement extends our analysis and treatment of social practices as recursive and presents more clearly the impact of practising as a leap of faith integral to the emerging novelty that characterizes entrepreneuring moment by moment. This perspective offers new theoretical and methodological avenues for advancing future entrepreneurship research and demonstrates how entrepreneuring is integral to other practices such as strategizing, project managing and leading. A new emplacement framework and illustrative case examples of entrepreneuring plant the seeds for a new chapter in the Entrepreneurship as Practice debate.